Social Representations of Cyberbullying in Parents and Teachers of a School in Lima in the Context of a Pandemic - Franco-Jiménez, Kimberly (2025)
After the arrival of the pandemic, not only the traditional forms of teaching-learning in schools changed, but also the violence, thus generating cyberbullying, in this regard, it is important to address what parents and teachers think about it. Thus, the objective is to know the social representations about cyberbullying in parents and teachers of a school in Lima in the context of pandemic. For this purpose, a qualitative research of reflexive thematic analysis design was carried out where 10 semi-structured interviews were applied to (5) teachers and (5) parents. It was found that, cyberbullying is perceived as a type of cyber violence among peers that manifests itself through verbal violence, as well as photo editing; also, the victims are perceived as introverted, the aggressors as lacking affection, and the spectators as normalizers of violence as entertainment. Regarding the contextualization of cyberbullying, participants point to dysfunctional family dynamics as the main cause, which generates emotional instability. Finally, regarding the coping of parents and teachers, the importance of involvement is found, and emphasis is placed on the prevention of the problem through different mechanisms. It is concluded that the participants represent cyberbullying as cyber violence, involving aggressors with affective deficiencies, introverted victims and bystanders who normalize violence. For their part, they indicate that the perpetrators come from families with dysfunctional dynamics; finally, they stress the need for active involvement and prevention on their part.